1989
DOI: 10.1083/jcb.109.6.2751
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-mediated autophosphorylation activity of the epidermal growth factor receptor during internalization.

Abstract: Abstract. The association of EGF with its receptor in endosomeS isolated from rat liver homogenates was assessed biochemically by polyethylene glycol precipitation and morphologically by electron microscope radioautography. The proportion of receptor-bound ligand in endosomes at 15 min after the injection of doses of 0.1 and 1 #g EGF/100 g body weight was 57 %. This value increased to 77 % for the dose of 10 /xg EGF injected. Quantitative electron microscope radioautography carried out on endosomes isolated at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 41 publications
4
53
0
Order By: Relevance
“…Other studies suggested that the tyrosine kinase itself plays a role in generating a lysosome targeting signal [27,28]. In accordance with this hypothesis, a greater and prolonged EGFR tyrosine phosphorylation has been demonstrated in rat liver endosomal membranes compared to the EGFR located at the plasma membrane [5,7,29,30]. The high phosphorylation content of internalized EGFR has been ascribed to a low dissociation and degradation state of EGF within the endosome [4,5,31].…”
Section: Discussionmentioning
confidence: 80%
“…Other studies suggested that the tyrosine kinase itself plays a role in generating a lysosome targeting signal [27,28]. In accordance with this hypothesis, a greater and prolonged EGFR tyrosine phosphorylation has been demonstrated in rat liver endosomal membranes compared to the EGFR located at the plasma membrane [5,7,29,30]. The high phosphorylation content of internalized EGFR has been ascribed to a low dissociation and degradation state of EGF within the endosome [4,5,31].…”
Section: Discussionmentioning
confidence: 80%
“…The fact that the membrane expression of EGFR in the MDCK 5aa cells was largely maintained even after 24 h of culture on polyHEMA (the time point with the highest EGFR activation) further supports juxtacrine activation of the EGFR. It is noteworthy that autocrine/paracrine activation of EGFR results in rapid receptor internalization and degradation (63).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, upstream components of ERK signaling, such as Ras and Shc, are accessible at the plasma membrane and endosomes (Di Guglielmo et al 1994;Haugh 2002). Although the ERK pathway may be activated globally, evidence suggests that the most potent activation of ERK occurs subsequent to internalization (Kay et al 1986;Lai et al 1989;Di Guglielmo et al 1994).…”
Section: Rtk Signaling: Plasma Membrane Versus Endosomementioning
confidence: 99%